ESTUDO DAS PROPRIEDADES CINÉTICAS DAS ISOFORMAS α 1 E α 2-3 Na+, K+ - ATPase EM CÓRTEX CEREBRAL E HIPOCAMPO DE RATOS - IGOR LEAL BRITO (2022)
Na+, K+-ATPase (NKA) is an electrogenic pump that maintains cellular homeostasis by transporting Na+ and K+ ions through the lipid bilayer. In the cells of the nervous system, NKA preserves the integrity of the neuron and the transmission of the nerve impulse. The deficiency in the catalytic activity of this ion pump in the brain is correlated with the development of different functional and cognitive neuropathies. Regions of the brain that regulate motor functions, memory and learning are the target for understanding the functioning of these neural processes. However, there are no studies on the catalytic properties of α 1, 2 and α 3 NKA isoforms in different regions of the brain. Thus, this study brings the characterization of the kinetic activity of α 1 and α 2-3 NKA in homogenates from cerebral cortex (CX) and hippocampus (HP). The activities of α 1 and α 2-3 NKA were quantified in HP and CX and in increasing concentrations of ATP, NaCl, KCl, MgCl2 and NH4Cl. The kinetic constants for α 1 and α 2-3 and total NKA (Km or K0.5, nH and Vmax) were determined for HP and CX. The results of this study demonstrate that the affinity of NKA to ions Na+, K+, Mg2+ and to ATP differs among the α isoforms of NKA and between the CX and HP brain regions. Furthermore, our data show that at low and high concentrations NH4+ can affect NKA activity in the CX, but appears to have little effect on the activity in the HP. Keywords: Kinetic characterization, α Na+, K+-ATPase, Hippocampus, Cerebral cortex and enzymatic activity.